2010
DOI: 10.1890/09-0293.1
|View full text |Cite
|
Sign up to set email alerts
|

Ecological drivers of the evolution of public‐goods cooperation in bacteria

Abstract: Abstract. The role of ecological processes in the evolution of social traits is increasingly recognized. Here, we explore, using a general theoretical model and experiments with bacteria, the joint effects of disturbance frequency and resource supply on the evolution of cooperative biofilm formation. Our results demonstrate that cooperation tends to peak at intermediate frequencies of disturbance but that the peak shifts toward progressively higher frequencies of disturbance as resource supply increases. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 26 publications
3
45
0
Order By: Relevance
“…Previous research has propounded the importance of ecology in social evolution and called for a deeper integration of ecological factors in social theory (69)(70)(71)(72)(73). Further to this claim, we suggest that ecological stressors could impact social evolution in microbes and in multicellular taxa more generally.…”
Section: Discussionsupporting
confidence: 53%
“…Previous research has propounded the importance of ecology in social evolution and called for a deeper integration of ecological factors in social theory (69)(70)(71)(72)(73). Further to this claim, we suggest that ecological stressors could impact social evolution in microbes and in multicellular taxa more generally.…”
Section: Discussionsupporting
confidence: 53%
“…The scenario we implement is one in which bacteria can achieve a basal growth rate by consuming a readily accessible carbon source, the basic nutrient N, which diffuses into the biofilm from the bulk liquid. Bacterial growth may be augmented by the activity of the secreted enzyme, which liberates a different growth substrate [89]. The two nutrient sources are implemented separately to allow us to independently vary the effects of two distinct phenomena on the evolution of cooperation.…”
Section: (C) Simulations With An Agent-based Modelmentioning
confidence: 99%
“…rspb.royalsocietypublishing.org Proc R Soc B 280: 20122770 public good compounds [94], the shapes of their benefit and cost functions [95], and disturbance-dispersal dynamics [89] also play an important role in the evolution of cooperation, but for the sake of illustration and brevity we have omitted these molecular and ecological details from our study.…”
Section: (C) Simulations With An Agent-based Modelmentioning
confidence: 99%
“…This framework models the ecological systems as a whole, including environmental features, such as the existence of limiting resources, but usually makes specific assumptions about the interactions among individuals. Experimental studies (Craig MacLean & Gudelj 2006, Brockhurst et al 2010) as well as analyses using the ecological framework, have shown that the limitation of resources might be important to explain cooperative behaviours in bacteria, plants, insects and even animals that do not posses enough information as to decide not to act as parasites. Some of these results are: the tradeoff between rate and yield of metabolic pathways, as that of aerobic and anaerobic bacteria, may foster cooperation in a two dimensional world (Pfeiffer et al 2001, Pfeiffer & Bonhoeffer 2003, Craig MacLean & Gudelj 2006; if trade of resources is possible, long term relationships allow cooperative plants to evolve (Mazancourt & Schwartz 2010); if the resource for which insects compete is the empty space left to lay eggs and they are not able to recognize their own eggs, cooperation, defection and coexistence are allowed (Mesterton-Gibbons 1991); if the individuals have the choice to parasite food items from their partners (kleptoparasitism, Broom & Ruxton 1998) all individuals will end up either always parasitizing or never doing it, and if the information about the amounts of food they will obtain is restricted, populations of cooperative individuals may evolve depending on the past history of the system (Broom & Rychtar 2009).…”
Section: Introductionmentioning
confidence: 99%